Principles of behavior change : understanding behavior modification techniques - Sarafino, Edward P., 1940- (John Wiley and Sons, 1996)
This book is divided into six parts: Overview and Basic Issues; Methods of Changing Operant Behavior; Methods of Changing Emotional Behavior and Associations; Program Design and Evaluation; Advanced and Specialized Methods in Behavior Modification; Present and Future Issues for Behavior Modification.